Applying genetic algorithm on power system stabilizer for stabilization of power system - Arnawan Hasibuan; . Syafrudin (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
This paper the genetic algorithm method is used in Power System Stabilizer (PSS) for power system stability is discussed. Parameters of PSS on generator system in a state determined offline using genetic algorithms and the objective function is based on eigen value system was described in detail. PSS parameters and the location is calculated to maximize damping performance in different operating conditions. Genetic algorithm is a kind of random search algorithm based on the mechanism of natural selection and natural genetics. Genetic algorithms are used as search parameters of the PSS technique, which utilizes genetic operators to find the nearest optimal solution. An advantage of the search with the GA is not trapped in an early convergence